Health Emergency Preparedness and Response Authority's (HERA) role in dealing with the monkeypox emergency in the European Union - Atanas Toshev; Elina Petkova-Gueorguieva; Anna Mihaylova; Galinka Pavlova; Nikoleta Parahuleva; Stefan Balkanski; Lily Peikova; Violeta Getova; Vasil Madzharov; Stanislav Gueorguiev (Pensoft Publishers, 2024)
The current article examines and analyzes the actions taken by the European Commission, specifically through the Directorate-General Health Emergency Preparedness and Response Authority (HERA) - an organization that anticipates threats and potential health crises, through intelligence gathering and building the necessary response capacities), aimed at supporting member states in limiting the spread of MPOX (monkeypox - an infectious disease caused by the monkeypox virus). It explores specific pharmaceutical products and vaccines procured by HERA and how they have been distributed among member states. The article raises questions about the compliance in purchasing pharmaceutical products and vaccines lacking approval for use within the European Union, highlighting the potential new regulatory challenges for Bulgaria if it needs to secure medications for treatment of human smallpox disease such as Jynneos and TPOXX (Tecovirimat) for its citizens. In conclusion, the article notes the swift response of HERA through the procurement of the Jynneos vaccine and TPOXX medicinal product. This swift response may have contributed to the decline of MPOX cases in the European region, potentially due to collaborative efforts among health authorities at both European and national levels. This success underscores the importance of cooperation among health authorities at various levels in combating infectious diseases.